Race to the canopy: the development of tree size hierarchies following a partial disturbance in a boreal old-growth forest - Kulha Niko; Ahokas Antti; Gauthier Sylvie; Aakala Tuomas (CANADIAN SCIENCE PUBLISHING, 2025)
In boreal old-growth forests, advance regeneration typically attains canopy dominance through growth release events fol-lowing partial disturbances. We sampled competing Picea mariana (Mill.) and Abies balsamea (L.) in disturbed old-growth stands in Quebec, Canada, to understand the intra-and interspecific size hierarchy development. We reconstructed tree size devel-opment and examined the role of initial size difference, time between germination and a disturbance, and the strength of response to the disturbance in determining tree size hierarchies. Trees that regenerated first generally dominated their in-traspecific competitors also following a disturbance event. However, prolonged time between germination and disturbance resulted in a less deterministic outcome. Tree size difference prior to disturbance also influenced the development of size hi-erarchies. In interspecific competition between individuals of the same diameter, A. balsamea had a 61% probability of gaining dominance over P. mariana, the probability being 50% if P. mariana was 5 mm larger than A. balsamea. Dominant trees generally had the strongest response to the disturbance, reinforcing the existing size hierarchies. The largest trees typically gain domi-nance after a partial disturbance. However, interspecific competition is less predictable than intraspecific competition, small initial size difference, and prolonged time in suppression potentially changing tree size hierarchies.